ANALISIS PERILAKU WIRAUSAHA DAN KINERJA USAHA (Studi Pada Usaha Agroindustri di Kota Pekanbaru) - Santoso, Edi; Restuhadi, Fajar; Yulida, Roza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Agricultural development with a focus on the development of processing industries base on agriculture products to in order accommodate raw materials of agriculture products and could absorb labor .This study aims to determine how internal and external factor agro-industry entrepreneurs, knowing how entrepreneurial behavior and performance of agro-industry enterprises. The location of this research in the city of Pekanbaru.The collection of data in this study using the method of survey.the sample in this research totaled 140 respondents. The data were analyzed using descriptive method. Data analysis result obtained from that internal factors of industrial entrepreneurs quite well with a value score of 3,14. External factors the businessman less good agro-indutries with a value score of 2,57. Entrepreneurial behavior of employers of agro-industries with a value of 3,88. The performance of venture entrepreneur agro-industries quite well with a value score of 3,07. Internal and external factors of agro-industries entrepreneurs can be enhanced by providing support to entrepreneurs in agro-industries such as providing counseling and training assistance-help needed by entrepreneurs in agro-industries and so created a better entrepreneurial behavior. And culminate in a good business the performance. Keyword: Entrepreneurial Behavior, the performance of the business, Agro-industries